Malaysian Halal Food Manufacturers' Venture into Global Markets: A Review - Mahmod Khalid, Almsafir; Kiandokht, Hadadi; Osman, Zain (2016)
International halal manufacturing endures to grow as an influential market dynamism in the global market. The halal trade includes the vast majority of manufacturing sub-sectors and shaped a profitable flea market. The main objective of this research is to explore on product characteristics and facilities that influence on Malaysian halal food products’ accessibility into the global markets. Therefore, the previous researches in Malaysian halal food products will be studied as well as its accessibility into the global markets. This paper is a review paper and based on previous studies, this research explored that the food safety, quality, hygiene and sanitation, ingredients, certification logo and food labeling, financial facilities, and logistics have a significant influence on Malaysian halal food products’ accessibility into the global markets.